Laboratory diagnosis of encephalitis: New insights into areas of uncertainty - Deema A Alokaili; Mustafa A Salih; Ali Mohammed Somily (Wolters Kluwer Medknow Publications, 2020)
Encephalitis is a serious clinical syndrome, which presents with a wide range of severity. Some cases might be missed due to non specific symptoms, especially in old debilitated patients and immunocompromised host. In this review, we cover the various clinical presentations of this syndrome and provide an overview of laboratory testing that can be performed in routine clinical microbiology laboratories and reference laboratories. Recently, the advance in medical care and advancing age of our patient population, as well as increased number of immunocompromised conditions either due to post chemotherapy, human immunodeficiency virus, transplant and autoimmune diseases complicated both clinical and laboratory diagnosis of encephalitis. Other noninfectious differential diagnoses of encephalitis should be ruled out with appropriate tests. There has been tremendous development in advanced laboratory testing including multiplex polymerase chain reaction, and next-generation sequencing requiring tedious validation and cost-effectiveness study to justify wise clinical utilization for these tests in the management of patients with encephalitis. Understanding of the interpretation of these new tests by treating physicians though better communication with medical microbiologists is required. Whole-genome sequencing is a new molecular test that enables us to detect a rare pathogen or even a new pathogen with a high degree of sensitivity and specificity if the standard recommendations are followed. The use of these tests should be available for specific clinical indications in an accredited reference laboratory for better utilization. Preanalytical parameters such as type of sample collected, tests requested, transportation, and storing of sample, could all affect the result of the test performed.